Study on Ademolus Hypoglycemic Index - Ademolu, Adegbenga B. (Highlights on Medicine and Medical Science Vol. 17, 2021)
Introduction: The ADEMOLUS HYPOGLYCEMIC INDEX (AHI) is proposed in this article as a mathematical representation of a hypoglycemic episode in a patient with recurrent hypoglycemia over a three-month period. Methodology: This is a retrospective analysis of 65 hypoglycemia episodes (HE) that occurred in six randomly selected diabetes mellitus patients from 86 case files analysed at the Lagos State University Teaching Hospital in Ikeja, Lagos, Nigeria. The data was examined using the Ademolus Hypoglycemia Classification and the 2018 ADA/EASD Hypoglycemia Classification to determine hypoglycemia. The proposed mathematical formula was used to derive AHI from the HE. The data was analysed using SPSS version 23. Results: The ADEMOLUS HYPOGLYCEMIC INDEX was used to investigate 65 hypoglycemic episodes in six diabetic patients. All six individuals experienced a succession of hypoglycemic episodes over the course of three months. Using both the ACH and the ADA/EASD classifications, Patient 1 had an AHI of 0.53. Discussion: In patient 1 her AHI was not in the severe range. In patient 3, in the last quarter of 2016, her AHI was 0.60, in the first quarter of 2017, her AHI was zero, then between June, July and August 2017 her AHI was 0.64. At this point in the patient's care, it would be prudent to assess the aetiological reasons in this diabetic patient with chronic kidney disease who suffers recurrent hypoglycemia, as it was six months ago. The formula can be programmed or computerized into a device like a calculator and/or a designed webpage calculator on ADEMOLUS HYPOGLYCEMIC INDEX can be developed. Conclusion: The Ademolus Hypoglycemic Index (AHI) is useful for tracking chronic or long-term recurrent HE in diabetic and non-diabetic patients.